ANALISIS PENGARUH ENVIRONMENT, SOCIAL, GOVERNANCE (ESG) SCORE TERHADAP RETURN SAHAM YANG TERDAFTAR DI INDEX IDX30 - Aditama, Fahreza (Contemporary Studies in Economic, Finance and Banking, 2022)
This study aims to examine the effect of the environmental, social, and governance (ESG) score on the company's stock returns. This study uses a sample of companies listed on the IDX30 Index from 2017-2020. The analysis technique used is in the form of multiple linear analysis using ESG score as the independent variable and stock return as a dependent variable and analyzed with the application of E-views 10. The results show that only the environmental score influences the company's stock returns. In further analysis, the social score and governance score do not affect the company's stock returns. Environmental score has a negative effect on stock returns. Companies must increase investment and assets if they want to reduce and limit the number of emissions issued in their business processes. This will affect the company's profitability so that it can influence investors' decisions.